A Comparison of Gas Exchange Models in the Estimation of CO2 Fluxes in the South Atlantic South of Africa for the Summer Season of 2008/2009 - Rainier, stephanie Megan (Department of Oceanography, 2024)
There is a problem in the determination of air-sea CO2 fluxes because of the number of different relationships used in calculating gas transfer velocities. There is also a problem with the CO2 sink in the Southern Ocean being greatly underestimated. Data were collected underway using an autonomous pCO2 system during three separate relief cruises over the course of austral spring 2008 to austral autumn 2009 onboard the RV SA Agulhas in the South Atlantic Ocean. The wind speed product was extracted from QuikSCAT. Using the data we investigated the sensitivity of the five gas transfer velocity parameterisations to the uncertainty in the wind speed product of 2m.s-1. We found that the Stagnant Film Model was unresponsive. Liss and Merlivat's (1986) linear model for three wind regimes showed a gradual increase in sensitivity with wind speed. The quadratic relationship developed by Nightingale et al., (2000) also showed a steady increase in sensitivity with an increase in wind speed. Wanninkhof's (1992) quadratic relationship showed the greatest response at low wind speeds and then a continuing increase in response through medium to high wind regimes. The cubic relationship from Wanninkhof and McGillis (1999) showed the smallest response at low wind speeds but had the greatest response to the uncertainty in the wind speed product in medium and high wind regimes. We also calculated regional and seasonal averages of the CO2 flux with the five gas transfer velocities based on the different relationships between gas transfer velocity and wind speed. We found that there was a CO2 flux into the ocean ranging from 4mmol.m-2.day-1 to 12mmol.m-2.day-1 between 33.5 and 68°S, except during autumn between 45-50°S where there is a flux out of the ocean of 2mmol.m2 .day-1. Between 68-70°S the flux into the ocean strengthens to between 28mmol.m2 .day-1 and 52mmol.m-2.day-1. Gas transfer velocity is not dependant on wind speed alone, but currently it is the only variable that it measureable on a global scale. Further investigations are in place to measure gas transfer velocity in situ. The Southern Ocean is greatly undersampled spatially and temporally which leads to a lack of understanding 13 about possibly one of the most important CO2 sinks. New methods are being taken on to increase the sampling resolution.